Konflik Internal Organisasi Nahdaltul Wathan di Lombok Timur - Supri, Supiandi; Nugroho, Wahyu Budi; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT This study analyzes conflicts that occur within Nahdlatul Wathan organizations. Furthermore the Nahdlatul Wathan organization is abbreviated to NW. This research uses qualitative approach-descriptive explanative type, and uses Conflict theory from Lewis A. Coser. forms of conflict according to Lewis A. Coser: Realistic, is the conflicts that seek to pursue power, status, and resources. while Non-Realistic conflict, which is seeking to decrease tensions.The Realistic conflict in NW organizations, are Conflict of the 10th NW Conference and Physical conflict of the post-10th Conference. Non-Realistic conflict in NW organization, are Debate of Maulana Shaykh's testament and Women's leadership in NW organization. Conflict Management of NW organization is resolving problems through deliberation and maintaining their unity through various activities. The NW Organization is continue to exist, as evidenced by the establishment of a variety of NW institutions from dahwah, social, and educational institutions. Keywords: NW conflict, forms of NW conflict, conflict management